Pengembangan Media Pengenalan Alat Musik Tradisional Sumatera Barat Berbasis Augmented Reality pada Mata Pelajaran Seni Budaya Siswa Kelas VIII SMP (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The limited availability of traditional musical instruments in schools is an obstacle in learning Arts and Culture, especially in the introduction of traditional musical instruments of West Sumatra for eighth grade junior high school students. This study aims to develop Augmented Reality (AR)-based learning media entitled Gema Adat Minang as a solution to this limitation. The study uses the Research and Development (R&D) method with a 4D development model that includes the Define, Design, Develop, and Disseminate stages. The study was conducted at SMP Negeri 3 Lubuk Basung. Data were obtained through validation questionnaires from material experts and media experts, as well as practicality questionnaires filled out by students. Media development involved 3D modeling of ten traditional musical instruments using Blender, AR application development with Unity 3D and Vuforia SDK, and interface and marker design using Canva. The results of the material expert validation showed an average value of 4.00 (100%) with a very valid category, while the media expert validation obtained an average value of 92% and 96% which were also in the very valid category. A practicality test on 30 students yielded an average score of 94%, categorized as very practical. These findings demonstrate that Gema Adat Minang is a valid and practical innovative learning tool for introducing traditional musical instruments using AR technology.